2017
DOI: 10.18006/2017.5(4).506.514
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of Trichoderma isolates on Sclerotium rolfsii

Abstract: Present study was carried out with an aim to screen potential Trichoderma strains to control Sclerotium rolfsii. Among the eleven isolates, Seven (T1, T3, T4, T5, T7, T9 and T11) were preliminarily identified as T. harzianum while the rest four (T2, T6, T8 and T10) were identified as T. viride. Further, results of study suggested that isolate T3, T4, T11, T2 and T10 were effective against S. rolfsii. Later, internal transcribed spacer (ITS)-1 sequence analysis confirmed isolate T3 as T. harzianum and T10 as T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…By pairing the culture of T. harzianum and Sclerotium rolfsi, Jana & Mandal (2017), found that up to 71% growth inhibition of S. rolfsi. Mousumi Das et al (2019) 2.2 ± 0.8 cA 2.0 ± 0.0 cA 1.0 ± 0.0 aA 1.0 ± 0.0 cA 3 Fusarium sp.…”
Section: Trichoderma Antagonism Analysismentioning
confidence: 99%
“…By pairing the culture of T. harzianum and Sclerotium rolfsi, Jana & Mandal (2017), found that up to 71% growth inhibition of S. rolfsi. Mousumi Das et al (2019) 2.2 ± 0.8 cA 2.0 ± 0.0 cA 1.0 ± 0.0 aA 1.0 ± 0.0 cA 3 Fusarium sp.…”
Section: Trichoderma Antagonism Analysismentioning
confidence: 99%